2016
DOI: 10.3917/spub.163.0399
|View full text |Cite
|
Sign up to set email alerts
|

La césarienne dans le contexte de gratuité au Bénin

Abstract: Introduction : Depuis 2009, le Bénin applique la gratuité de la césarienne pour en améliorer l’accessibilité financière. La présente étude visait à décrire la césarienne dans le contexte de gratuité au Bénin en 2013. Méthodes : Étude transversale descriptive qui a impliqué les femmes accouchées par césarienne, de décembre 2013 à février 2014 dans douze hôpitaux sélectionnés par choix aléatoire simple dans chaque département du Bénin. Les données quantitatives collectées par exploitation des dossiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 39 Even if the free policy was not totally effective, the monetary burden was less important for women after the reform. 40 …”
Section: Discussionmentioning
confidence: 99%
“… 39 Even if the free policy was not totally effective, the monetary burden was less important for women after the reform. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Second, this study did not consider the level of implementation of the free C-section policy in both countries. Previous studies showed that the cost of C-sections was still high in many hospitals in Benin after the policy was introduced [ 15 ] and that 91% of women still paid for their C-sections in a rural area of Mali during the period 2008–2011 [ 51 ]. The impact of this policy on socioeconomic inequalities might have been more important than the observed impact if C-sections were truly free for every woman.…”
Section: Discussionmentioning
confidence: 99%
“…In April 2009, the government of Benin introduced a national user fee exemption policy concerning all C-sections in selected public and private hospitals that offer emergency obstetric care. Hospitals receive 100,000 CFA (US$166) per C-section, which covers pre-operative laboratory tests, medications, surgery kits, blood, hospitalization for 7 days and transportation to a hospital if the woman is referred [ 15 , 16 ]. The state is the principal financer of the reform [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these health policies is the free caesarean section, which was started in Benin in 2009 [8]. In practice, hospitals are paid a fat fee of CFA francs 100.000 (US$152.08) per caesarean section [9]. Tis measure helped bring the caesarean delivery rate to 5.1% and the participation rate by qualifed health personnel to 78.0% in Benin in 2019 [3].…”
Section: Introductionmentioning
confidence: 99%